Synthesis and properties of some pyrazole derivatives of 1,2,4-triazole-3-thiol - A. S. Hotsulia; S. M. Kulish (Zaporozhye State Medical University, 2020)
Nitrogen-containing heterocyclic compounds play an important role in the modern pharmaceutical industry. This is due to their significant biological potential. 1,2,4-Triazole and pyrazole are known pharmacophores that are responsible for the formation of a wide range of activities. The construction of the target molecule using 1,2,4-triazole and pyrazole is also interesting in terms of the availability of starting reagents and the simplicity of chemical transformations. The combination of these heterocycles in one molecule allows increasing its opportunities of participation in various biological processes. The aim of the research was to examine the conditions for obtaining S-alkylderivatives of 5-(5-methylpyrazole)-4-ethyl-1,2,4-triazole-3-thiol and to investigate these compounds' properties. Materials and methods. The first phase of the research involved the use of diethyloxalate, acetone and sodium methylate as starting substances for the synthesis of the intermediate. The obtained methyl 2,4-dioxopentanoate in the following step was converted into 5-methylpyrazole-3-carbohydrazide with the double amount of hydrazine hydrate. The subsequent modification of the molecule implied a stepwise use of the reactions of nucleophilic addition of ethyl isothiocyanate and alkaline cyclization. Thus, the obtained 5-(5-methylpyrazole)-4-ethyl-1,2,4-triazole-3-thiol became subject to an alkylation process. To establish the composition and identify the structure of the isolated substances, 1H NMR and infrared spectra were recorded, as well as qualitative and quantitative indicators of the elemental composition of the synthesized structures were obtained. The individual nature of the presence of substances and the degree of their purity were determined using high performance liquid chromatography with two types of detection: diode-matrix and mass spectrometric. Results. The synthesis of alkylderivatives of 5-(5-methylpyrazole)-4-ethyl-1,2,4-triazole-3-thiol was carried out and the optimal conditions for the process of obtaining these substances were determined. The structure of the products of chemical transformation is confirmed and the results of the study of its physical properties are recorded. The results of docking studies allowed to confirm the prospects of the chosen direction of synthetic transformations, which ultimately allowed to determine the biological potential of the obtained compounds. The model enzymes were kinase of the anaplastic lymphoma (code 2XP2), 14-alpha demethylase of the lanosterol (code 3LD6) and cyclooxygenase-1 (code 3N8Y), information on which was obtained from the Protein Structures Database (PDB). Conclusions. Molecular docking resulted in obtaining data that form a concept of a certain level of probability of synthesized compounds' influence on the activity of these enzyme structures.